Leibniz and the Molyneux Problem - Bridger Ehli (Journal of Modern Philosophy, 2020)
The Molyneux problem is one of the major questions addressed by early modern authors. Whereas Locke’s response to Molyneux’s question has been the subject of extensive scholarly discussion, Leibniz’s response has received comparatively little attention. This paper defends an interpretation of Leibniz’s nuanced response to the problem and criticizes a competing interpretation that has recently been proposed.